Analisis Kesesuaian Lahan Permukiman Menggunakan Sistem Informasi Geografis Di Kota Binjai - Geniusmaniat Laia; Zulkifli Nasution; Achmad Siddik Thoha (Fakultas Teknik, 2020)
A determination location for residential areas was influenced by physical factors, accessibility, socioeconomics, existing land use conditions, etc. Binjai is a municipality that has the highest population growth and resulting in the development of settlement highest growth. It is necessary to analyze land suitability for settlement development that provides appropriate residential location direction to realize productive and effective land use by utilizing Geographic Information Technology (GIS). This study aims to analyze residential development direction in Binjai as well as determine potential location into a residential area by considering carrying land capacity, land use effectiveness, and productivity. The suitability land capacity analysis for settlements development results: Very High (ST) 2,616.12 Ha, High (T) 4,295.65 Ha, Medium (S) 2,332.15 Ha, Low (R) 465.67 Ha, and Very Low (SR) 65.16 Ha. Suitability effectiveness analysis for settlements development results: Very High (ST) 4,560.08 Ha, High (T) 2,636.54 Ha, Medium (S) 1,533.04 Ha, Low (R) 417.36 Ha, and Very Low (SR) 167.65 Ha. Conformity analysis productivity utilization for settlements development results; Very High (ST) 4,216.52 Ha, High (T) 2,036.35 Ha, Medium (S) 1,249.72 Ha, Low (R) 1,122.23 Ha, and Very Low (SR) 451.52 Ha.